CASPT2 Study of the Unimolecular Reactions of Nitromethane—A Look at the Roaming Reactions in the Decomposition of Nitromethane: An Exergonic Route at High Temperatures. - Soto-Martín, Juan (MDPI, 2025)
In this work, we studied the main decomposition reactions on the ground state of nitromethane (CH3NO2) with the CASPT2 approach. The energetics of the main elementary reactions of the title molecule have been analyzed on the basis of Gibbs free energies obtained from standard expressions of statistical thermodynamics. In addition, we describe a mapping method (orthogonalized 3D representation) for the potential energy surfaces (PESs) by de ning an orthonormal basis consisting of two Rn orthonormal vectors (n, internal degrees of freedom) that allows us to obtain a set of ordered points in the plane (vector subspace) spanned by such a basis. Geometries and harmonic frequencies of all species and orthogonalized 3D representations of the PESs have been computed with the CASPT2 approach. It is found that all of the analyzed kinetically controlled reactions of nitromethane are endergonic. For such a class of reactions, the dissociation of nitromethane into CH3 and NO2 is the process with the lower activation energy barrier (∆G); that is, the C-N bond cleavage is the most favorable process. In contrast, there exists a dynamically controlled process that evolves through a roaming reaction mechanism and is an exergonic reaction at high temperatures: CH3NO2 → [CH3. . .NO2]* → [CH3ONO]* → CH3O + NO. The above assertions are supported by CASPT2 mappings of the potential energy surfaces (PESs) and classical trajectories obtained by “on-the y” CASSCF molecular dynamics calculations.
Keywords: Quimioinformática; Estructura electrónica; Nitrocompuestos; Compuestos organonitrogenados; Reacciones químicas; CASSCF; CASPT2; Nitromethane; Exergonic decomposition